Effect of severe renal impairment on pharmacokinetics, safety, and tolerability of lemborexant - Landry, Ishani; Aluri, Jagadeesh; Hall, Nancy; Filippov, Gleb; Dayal, Satish; Moline, Margaret; Reyderman, Larisa (Pharmacology research & perspectives, 2021)
The primary aim of this study was to examine the effect of severe renal impairment (SRI) on the pharmacokinetics of lemborexant, a dual orexin receptor antagonist indicated for the treatment of insomnia. A phase 1 multicenter, single‐dose, open‐label, parallel‐group study was conducted in subjects with SRI not requiring dialysis (estimated glomerular filtration rate 15–29 ml/min/1.73 m2; n = 8) compared with demographically matched healthy subjects with normal renal function (n = 8). Plasma levels of lemborexant and its metabolites were measured over 240 h following a single oral 10‐mg dose administered in the morning. Relative to subjects with normal renal function, lemborexant maximum plasma concentration (Cmax) was similar, whereas area under the plasma concentration–time curve from zero to time of last quantifiable concentration (AUC(0‐t)) and AUC from zero to infinity (AUC(0‐inf)) were about 1.5‐fold higher in subjects with SRI. The geometric mean ratios (90% confidence interval) were 104.8 (77.4–142.0), 150.5 (113.2–200.3), and 149.8 (113.1–198.6) for Cmax, AUC(0‐t), and AUC(0‐inf), respectively. In both groups, the median lemborexant time to Cmax (tmax) was 1 h, and the mean unbound fraction of lemborexant was ~7%. For the M4, M9, and M10 metabolites, Cmax was reduced ~20% and exposure (AUC(0‐t) and AUC(0‐inf)) was ~1.4‐ to 1.5‐fold higher in subjects with SRI versus healthy subjects; tmax was delayed ~1.5–2 h for M4 and M10. All treatment‐emergent adverse events were mild or moderate. Lemborexant pharmacokinetics were not sufficiently altered to warrant a dose adjustment for subjects with renal impairment. Lemborexant is a dual orexin receptor antagonist approved for the treatment of adults with insomnia. Lemborexant tmax and Cmax were not altered in subjects with severe renal impairment compared with healthy subjects, but exposure (AUC) was increased approximately 1.5‐fold. Lemborexant has a favorable safety profile and dosing is initiated at 5 mg, which can be increased based on efficacy and tolerability. Thus, these results support the use of lemborexant in subjects with mild to severe renal impairment without dosing adjustment.